A SCREENING METHOD FOR C2 EXPERT ASSESSMENT (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Although it is widely recognized that simulations based on particular scenarios are the best Measures of Force Effectiveness (MoFE) and Measures of Command and Control Systems (C2) Effectiveness (MoCE), a generalized assessment of the entire C2 system or certain it’s parameters for particular practical and research purposes is required. Current report presents a screening method for C2 expert assessment, built on the basis of a detailed analysis of the Doctrine of the Bulgarian armed forces in its chapter "Leadership, command and control of the armed forces". The Measures of Performance (MoP), namely the focus on internal system structure, characteristics and behaviour and the Dimensional Parameters (DP) - the focus on the properties or characteristics inherent in the physical C2 systems are used as underlying, intrinsic principles. The purpose of constructing and applying the method is to present a general rough picture of the state of C2 and to mark the areas of its strengths and weaknesses. Through changes in the instruction and in certain items, the questionnaire can be applied to different contexts. The separate structural blocks of the questionnaire assess aspects of the three levels of commands and the complex capabilities of their bodies, the practical and technical parameters of the available Communication and Information system (CIS), etc. After a validation process, the method can be used as a convenient tool for educational, scientific and practical purposes.